IMF Research Bulletin, September 2015. (IMF Research Bulletin; IMF Research Bulletin ;, 2015)
The September 2015 issue of the IMF Research Bulletin covers a range of research topics. The Research Summaries featured in this issue are 'Lower for Longer: Neutral Rates in the United States' (Andrea Pescatori and Jarkko Turunen) and 'Economic Principles for Resource Revenue Management' (Anthony J. Venables and Samuel Wills). The Q and A article looks at 'Seven Questions on Financing for Development' (Amadou Sy) and the global development agenda. The issue also includes special announcements on the 2015 Annual Research Conference and the 2015 IMF Annual Report, as well as new IMF publications. Readers will also find a link to a top-viewed article from the 'IMF Economic Review'-the IMF's official research journal.